TOWARDS A METHODOLOGY TO ESTIMATE MINIMUM SAMPLE LENGTH FOR SPEAKING RATE - Arantes, Pablo; Lima, Verônica Gomes (Revista do GEL, 2017)
The aim of the present work is to investigate how long should a speech sample be for the speaking rate derived from it can be considered representative of the whole utterance from which the sample has been taken. Eight Brazilian Portuguese speakers read a 144-word text in three rate levels: slow, normal and fast. Speaking rate was measured cumulatively as the number of phonetic syllables per second from the first to the last syllable in the sample. Two types of rates were measured, speech rate and articulation rate. Change point analysis was used to determine the influence of rate type and level on the amount of time necessary for the cumulative estimate of speech and articulation rates to stabilize around the rate yielded by the whole utterance. Mean stabilization latencies are 9.2 seconds for speech rate and 8.7 s for articulation rate. The slow rate tends to stabilize later than fast and normal rates for both types of rate. Stabilization intervals take up a median number of 41 (speech rate) and 59 (articulation rate) syllables. Mean deviation between the global rate and the rate value at stabilization point are 7.8% (speech rate) and 4.2% (articulation rate).